THE INFLUENCE OF RELIGIOSITY, INCOME AND INFORMATION MEDIA ON INTEREST IN WAQF MONEY (Studi At the ZISWAF Laboratory, Faculty of Islamic Economics And Business, Uin Fatmawati Sukarno Bengkulu) - Harjoalmi, Weli Agustina; Isnaini, Desi; Cahyono, Andi; Afrianty, Nonie; Yuniara, Yuyun (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The purpose of this study is to analyse the effect of religiosity, income and information media on interest in waqf money at the Zakat Infaq Sedekah and waqf Laboratory of the Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu. This research is a type of field research with a quantitative approach. The population in this study were alumni and lecturers of the Faculty of Economics and Islamic Business of UIN Fatmawati Sukarno Bengkulu who made cash waqf in the last 3 years totalling 1,102 and the sample taken was 10% of 1,102, namely 110 people. The data collection techniques used were questionnaire observation and documentation. Based on the results of the study, it can be concluded that there is an influence of religiosity, income and information media on the interest in waqf money at the Zakat Infaq Sedekah and Waqf Laboratory of the Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu. Evidenced by the sig. value of 0.00 <0.05